2013
DOI: 10.1159/000350486
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Effects of Omalizumab in Children with Severe Refractory Atopic Dermatitis: A Randomized, Placebo-Controlled Clinical Trial

Abstract: Background: Severe refractory atopic dermatitis (AD) is a chronic, debilitating condition that is associated with elevated serum immunoglobulin E (IgE) levels. Thymic stromal lymphopoietin (TSLP), thymus and activation-regulated chemokine (TARC) and OX40 ligand (OX40L) are important immunologic factors involved in the pathogenesis of AD. Omalizumab, an anti-IgE antibody indicated for use in allergic asthma, is implicated in regulating allergen presentation by dendritic cells and the T cell response during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
124
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 45 publications
2
124
0
4
Order By: Relevance
“…It seems that Xolair could be effective in decreasing IgE levels in different doses and durations of the treatment, although, the decrease of IgE level is not important on its own. Some studies showed that the decrease of IgE did not associate with clinical resolutions (9,11). Clinical manifestations improved in all of the studies (3,(8)(9)(10)(11)(12)(13)(14) except one, other researches had no control group.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…It seems that Xolair could be effective in decreasing IgE levels in different doses and durations of the treatment, although, the decrease of IgE level is not important on its own. Some studies showed that the decrease of IgE did not associate with clinical resolutions (9,11). Clinical manifestations improved in all of the studies (3,(8)(9)(10)(11)(12)(13)(14) except one, other researches had no control group.…”
Section: Discussionmentioning
confidence: 92%
“…Serum IgE level was increased in all patients. Only one of those studies included a control group (11). AD were associated with other allergic disorders such as asthma and allergic rhinitis (AR) in all patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations